Education of the importance of consuming vegetables and fruit for teenagers to maintain stamina at MAN 2 Sleman - Florentina Kusyanti; Sukmawati Sukmawati (Universitas Muhammadiyah Magelang, 2023)
Currently, many teenagers in modern times generally do not want to eat vegetables and fruit. They tend to prefer to eat fast food. In fact, eating fast food has a negative impact on the health of the body. Meanwhile, fruits and vegetables contain lots of vitamins, proteins, and fats which are very useful for the body. The purpose of this service is to provide an understanding of the ingredients found in vegetables and fruit, as well as their benefits for the health of adolescents in maintaining body stamina. The method used in the service is the lecture method with presentation techniques, followed by a question-and-answer discussion. The results of the community service activities which were attended by 90 students of MAN 2 Sleman grades X-XII showed that before the activity, many students did not like vegetables, but after receiving the material many said they liked it because they did not know the benefits and the taste was not good. In addition, they will try to eat fruit even if their parents don't peel it and prepare it at the dinner table, especially for young women so that their skin looks fresh.